Molecular analysis of pyrazinamide resistance in Mycobacterium tuberculosis in Vietnam highlights the high rate of pyrazinamide resistance-associated mutations in clinical isolates<subtitle>PncA mutations and PZA resistance in M. tuberculosis in Vietnam</subtitle> - Nguyen Quang Huy; Contamin Lucie; Tran Thi Thanh Hoa; Nguyen Van Hung; Nguyen Thi Ngoc Lan; Nguyen Thai Son; Nguyen Viet Nhung; Dang Duc Anh; Bañuls Anne-Laure; Nguyen Thi Van Anh (Emerging Microbes and Infections, 2017)
Pyrazinamide (PZA) is a key antibiotic in current anti-tuberculosis regimens. Although the WHO has stressed the urgent need to obtain data on PZA resistance, in high tuberculosis burden countries, little is known about the level of PZA resistance, the genetic basis of such resistance or its link with Mycobacterium tuberculosis families. In this context, this study assessed PZA resistance through the molecular analysis of 260 Vietnamese M. tuberculosis isolates. First-line drug susceptibility testing, pncA gene sequencing, spoligotyping and mycobacterial interspersed repetitive units-variable number of tandem repeats (MIRU-VNTR) typing were performed. Overall, the pncA mutation frequency was 38.1% (99 out of 260 isolates) but was higher than 72% (89 out of 123 isolates) in multidrug and quadruple-drug resistant isolates. Many different pncA mutations (71 types) were detected, of which 55 have been previously described and 50 were linked to PZA resistance. Among the 16 novel mutations, 14 are likely to be linked to PZA resistance because of their mutation types or codon positions. Genotype analysis revealed that PZA resistance can emerge in any M. tuberculosis cluster or family, although the mutation frequency was the highest in Beijing family isolates (47.7%, 62 out of 130 isolates). These data highlight the high rate of PZA resistance-associated mutations in M. tuberculosis clinical isolates in Vietnam and bring into question the use of PZA for current and future treatment regimens of multidrug-resistant tuberculosis without PZA resistance testing.Emerging Microbes & Infections (2017) 6, e86; doi:10.1038/emi.2017.73; published online 11 October 2017